Towards Religiosity-Based Legal Science: Critical-Constructive Prophetic Law on Positivism Paradigm - Santoso, Lukman (Universitas Islam Indonesia, 2020)
Positivism, which is the spirit of modern legal development, has brought legal science to an increasingly ridiculous realm, resulting in the collapse of public trust in legal institutions. The alienation of legal principles such as the substance and legal structure of the religious value also contributes to this distrust. Thus, it is necessary to make a philosophical criticism of the legal positivism paradigm. This research is doctrinal research using a philosophical approach. The data collection technique was conducted by using a research library. The results of this study provide findings. First, the urgency of a philosophical criticism of the positivism paradigm is based on that this paradigm has taken the law away from the values of religious morality. Ideally, in the framework of prophetic law, law is not only a human affair, but as an embodiment of divine values. Second, critical-constructive prophetic law rests on the development of legal science based on transcendental religious values. The application in the Indonesian context is to synergize the pillars of humanization, liberation and transcendence within the framework of the rule of law Pancasila. Therefore, the law can benefit all. The contribution of this study will further strengthen the building of Indonesian law which is divinity, humanity, unity, democracy, and justice.Keywords: Positivism; Paradigm; Prophetic Law; TranscendentalMenuju Ilmu Hukum Berbasis Agama: Kritis-Konstruktif Hukum Profetik pada Paradigma PositivismeAbstrakPositivisme yang menjadi semangat perkembangan hukum modern telah membawa ilmu hukum ke ranah yang semakin menggelikan, sehingga mengakibatkan runtuhnya kepercayaan masyarakat terhadap lembaga hukum. Keterasingan asas-asas hukum seperti substansi dan struktur hukum nilai agama turut berkontribusi terhadap ketidakpercayaan ini. Oleh karena itu, perlu dilakukan kritik filosofis terhadap paradigma positivisme hukum. Penelitian ini merupakan penelitian doktrinal dengan menggunakan pendekatan filosofis. Teknik pengumpulan data dilakukan dengan menggunakan penelitian kepustakaan. Hasil penelitian ini memberikan temuan. Pertama, urgensi kritik filosofis terhadap paradigma positivisme didasari bahwa paradigma ini telah menjauhkan hukum dari nilai-nilai moralitas agama. Idealnya, dalam kerangka hukum profetik, hukum bukan hanya urusan manusia, tetapi sebagai pengejawantahan nilai-nilai ketuhanan. Kedua, hukum profetik kritis-konstruktif bertumpu pada pengembangan ilmu hukum yang berlandaskan nilai-nilai agama transendental. Penerapannya dalam konteks Indonesia adalah mensinergikan pilar humanisasi, liberasi, dan transendensi dalam kerangka negara hukum Pancasila. Oleh karena itu, hukum dapat bermanfaat bagi semua. Kontribusi penelitian ini akan semakin memperkuat bangunan hukum Indonesia yang ketuhanan, kemanusiaan, persatuan, demokrasi, dan keadilan.Kata kunci: Positivisme; Paradigma; Hukum Profetik; Transendental